2013
DOI: 10.1051/0004-6361/201219165
|View full text |Cite
|
Sign up to set email alerts
|

Binary black holes in nuclei of extragalactic radio sources

Abstract: If we assume that nuclei of extragalactic radio sources contain binary black hole systems, the two black holes can eject VLBI components, in which case two families of different VLBI trajectories will be observed. Another important consequence of a binary black hole system is that the VLBI core is associated with one black hole, and if a VLBI component is ejected by the second black hole, one expects to be able to detect the offset of the origin of the VLBI component ejected by the black hole that is not assoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 44 publications
2
39
0
Order By: Relevance
“…2000; Romero et al 2000;Caproni & Abraham 2004a,b;Caproni et al 2006Caproni et al , 2013Roland et al 2013). The parsec-scale jet of PG 1553+113 is assumed to be associated with the primary SMBH.…”
Section: An Smbh Binary System In Pg 1553+113mentioning
confidence: 99%
“…2000; Romero et al 2000;Caproni & Abraham 2004a,b;Caproni et al 2006Caproni et al , 2013Roland et al 2013). The parsec-scale jet of PG 1553+113 is assumed to be associated with the primary SMBH.…”
Section: An Smbh Binary System In Pg 1553+113mentioning
confidence: 99%
“…Roland et al (2013) attempted to explain the different trajectories followed by the knot C5 and knot C10 in terms of a binary black hole system.…”
mentioning
confidence: 99%
“…It has been suggested by Lister & Homan (2005) that the lowest values for the error bars should be ≈beam/5, but Roland et al (2013) showed that the correct lowest values for the error bars adopted at 15 GHz are given by beam/15 ≤ ∆ min ≤ beam/12.…”
Section: Radio Source 1928+738mentioning
confidence: 99%
“…The possible free parameters of the model (for more details see Roland et al 2013) are -i o the inclination angle; -φ o the phase of the precession at t = 0; -∆Ξ the rotation angle in the plane perpendicular to the line of sight, also the asymptotic direction of the jet; -Ω the opening angle of the precession cone; -R o the maximum amplitude of the perturbation; -T p the precession period of the accretion disk; -T d the characteristic time for the damping of the beam perturbation, -M 1 the mass of the black hole ejecting the radio jet; -M 2 the mass of the secondary black hole; -γ c the bulk Lorentz factor of the VLBI component; -ψ o the phase of the BBH system at t = 0; -T b the period of the BBH system; -t o the time of the origin of the ejection of the VLBI component; -V a the propagation speed of the perturbations; -n rad is the number of steps to describe the extension of the VLBI component along the beam; -∆W and ∆N the possible offsets of the origin of the VLBI component.…”
Section: Model Parametersmentioning
confidence: 99%